2014
DOI: 10.1371/journal.pone.0093271
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Global Expression of MicroRNAs in an Experimental Model of Physiological Left Ventricular Hypertrophy

Abstract: BackgroundMicroRNAs (miRs) are a class of small non-coding RNAs that regulate gene expression. Studies of transgenic mouse models have indicated that deregulation of a single miR can induce pathological cardiac hypertrophy and cardiac failure. The roles of miRs in the genesis of physiological left ventricular hypertrophy (LVH), however, are not well understood.ObjectiveTo evaluate the global miR expression in an experimental model of exercise-induced LVH.MethodsMale Balb/c mice were divided into sedentary (SED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 50 publications
1
41
0
Order By: Relevance
“…Recently, miR-150 was also found to be a modulator of physiological cardiac hypertrophy in response to exercise (21). Whether increase of plasma miR-150 levels relates to cardiovascular exercise-induced adaptation, i.e., left ventricular hypertrophy or the increased mobilization of EPCs, remains to be experimentally validated in an in vivo animal model of physical exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, miR-150 was also found to be a modulator of physiological cardiac hypertrophy in response to exercise (21). Whether increase of plasma miR-150 levels relates to cardiovascular exercise-induced adaptation, i.e., left ventricular hypertrophy or the increased mobilization of EPCs, remains to be experimentally validated in an in vivo animal model of physical exercise.…”
Section: Discussionmentioning
confidence: 99%
“…miR-1, miR-133, miR199a/b, miR-21, miR-23, miR-26, miR-29, miR-9, miR-98, and miR-499) have been shown to exert either a positive or negative influence on pathological cardiac hypertrophy (4 -6). Whereas several studies have recently profiled microRNA expression signatures in rat physiological hypertrophic hearts induced by swimming or treadmill training, it still remains unknown how dys-regulated miRNAs contribute to physiological hypertrophy (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…In exercised rats, miR-27a and -27b were reported to increase while miR-143 decreased, together with reciprocal changes in expression of their angiotensin-converting enzyme targets, ACE and ACE2, respectively, suggesting specific miRNAs targeting renin -angiotensin system genes are dynamically modulated by exercise training and may contribute, at least in part, to the progression of cardiac hypertrophy . Using a microarray to assess .1000 murine miRNAs in exercise-induced LV hypertrophy, Martinelli et al (2014) identified 35 miRNAs differentially expressed after 1 week of exercise relative to sedentary controls and 25 miRNAs differentially expressed after 5 weeks of training, documenting temporal regulation of cardiac miRNAs during exercise training. We profiled miRNAs in hearts of mice subjected to 3 weeks of either an intense swimming protocol or voluntary wheel running.…”
Section: Micrornas In Cardiovascular Exercise Responsementioning
confidence: 99%
“…In contrast, fewer studies have directly examined the functional role of miRNAs in physiological cardiac hypertrophy Soci et al 2011;Liu et al 2015). However, multiple studies have identified cardiac miRNAs differentially regulated in exercise, which were known to regulate pathological hypertrophy, including miRNAs in Table 1 (Care et al 2007;Fernandes et al 2011;Soci et al 2011;Ma et al 2013;Martinelli et al 2014;Liu et al 2015). Thus, although the functional contributions of most have not been directly assessed in exercise-induced hypertrophy, these miRNAs may also modulate physiological hypertrophy.…”
Section: Functional Contributions Of Mirnas To Exercise Phenotypes Camentioning
confidence: 99%
See 1 more Smart Citation